Analysis of the Effectiveness and Efficiency of Village Fund Budgeting for the Maintenance of Farm Roads: A Case Study of Anugrah Village, Lantari Jaya District, Bombana Regency - Nita Hansita; Novi Kristiani Saputri; Muh. Nur; Yusuf Jaya Saputra; Supriyadi; Reyhan Dzikriansyah Suanrno dzikriansyah (Ikatan Cendekiawan Muda Akuntansi (ICMA), 2026)
This research aims to determine and analyze the effectiveness and efficiency of village fund budgets in efforts to maintain farm roads. This research uses a qualitative descriptive method with the data used coming from primary data in the form of interviews and secondary data through documentation. The results of this research show that based on the results of the analysis previously presented, it can be concluded that the effectiveness and efficiency of the village fund budget in efforts to improve farming roads in Anugrah Village can be said to be efficient but still less effective. This is because the village budget is still limited by regulations, the obstacle faced is the lack of Village Funds to finance all programs and the climate conditions in Anugrah Village.